L’échec et la splendeur : les allégories du baroque moderne dans l’œuvre d’Octavio Paz - Marcos Rico Domínguez (IdeAs)
This article addresses the theoretical, cultural, literary and artistic examination by Octavio Paz of the baroque and its relationship to modernity in his book devoted to the seventeenth-century Mexican poet, Sor Juana (Sor Juana: Or, the Traps of Faith). This study concerns itself with the preference Paz displays for analogy and allegory, along with his vision of modernity as a tradition born out of the ruins of a lost world (ancient prehispanic civilizations) and as the outgrowth of a displaced foreign literature: Mexican baroque. For Paz, the Spanish baroque and Hispanic-American context form a dialogical relationship, in which Catholicism retains the influence of paganism and compounds a plurality of cultural and social discourses. Paz’s “excremental baroque” (Conjunctions and Disjunctions) forms a style that retains a sense of language’s vitality with respect to “escatológicos” materials (scatological and eschatological). For example, Paz identifies in baroque art the presence of Eros, embodying both splendor and decline, which he associates with the experience of the body and the relation that arises with language. His thinking extends into his long prose poem, The Monkey Grammarian, which takes up the principal themes of his poetry.